2019
DOI: 10.1111/cmi.13144
|View full text |Cite
|
Sign up to set email alerts
|

Two isotypes of phosphatidylinositol 3‐phosphate binding sorting nexins play distinct roles in trogocytosis in Entamoeba histolytica

Abstract: Phosphatidylinositol phosphates (PIPs) function as important second messengers in many cellular events. In the human intestinal protist Entamoeba histolytica, where phagocytosis/trogocytosis plays an indispensable role in proliferation and pathophysiology during infection, various PIPs are involved in multiple steps of phago/trogocytosis. PI3-phosphate (PI3P) plays a pivotal role in the biogenesis of phagosome/trogosomes via recruitment of PI3P effectors. Because no known PI3P downstream effectors are conserve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
51
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
2

Relationship

5
3

Authors

Journals

citations
Cited by 24 publications
(52 citation statements)
references
References 34 publications
1
51
0
Order By: Relevance
“…A similar dependence on the prey was previously demonstrated for PI3P recruitment to phagosomes. GFP-HrsFYVE, a PI3P bioprobe, was recruited to phagosomes that contained serum-coated beads, but not to those containing non-coated beads in E. histolytica [ 3 , 6 ]. Furthermore, it was demonstrated that the trogocytosis of CHO was enhanced while the phagocytosis of non-coated beads was repressed by HrsGFP-FYVE overexpression [ 3 ], suggesting that the role of PI3P may differ in live cell trogocytosis and bead phagocytosis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A similar dependence on the prey was previously demonstrated for PI3P recruitment to phagosomes. GFP-HrsFYVE, a PI3P bioprobe, was recruited to phagosomes that contained serum-coated beads, but not to those containing non-coated beads in E. histolytica [ 3 , 6 ]. Furthermore, it was demonstrated that the trogocytosis of CHO was enhanced while the phagocytosis of non-coated beads was repressed by HrsGFP-FYVE overexpression [ 3 ], suggesting that the role of PI3P may differ in live cell trogocytosis and bead phagocytosis.…”
Section: Discussionmentioning
confidence: 99%
“…The significance of PIPs, particularly PI3P and PI(3,4,5)P 3 , in the trogo- and phagocytosis of E. histolytica has been well documented [ 3 , 4 , 5 ]. It has been shown that PI3P, monitored by Hrs-FYVE (Fab-1, YGL023, Vps27, EEA1) and sorting nexin 1 (SNX1) as its biosensor, is recruited to the bottom of the trogo- and phagocytic cups, and subsequently to trogo- and phagosomes [ 3 , 6 ]. On the other hand, the E. histolytica FYVE domain containing protein 4 (FP4), which binds to PI4P, has been shown to be recruited to the neck of the closing trogocytic cup and closed (mature) trogosomes [ 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…While effectors and binding proteins for EhRab7D remain elusive, the effector of EhRab7A was previously demonstrated (Nakada-Tsukui et al, 2005). Retromer complex, the EhRab7A effector, is assumed to be involved in the forward transport of hydrolytic enzymes or their cargo receptors to trogosomes and phagosomes or in the transport in a reverse direction in E. histolytica (Nakada-Tsukui et al, 2005;Picazarri et al, 2015;Watanabe et al, 2020 Figure S2). This inter-switch region was reported to be an interface between Rab7 and Rab interacting lysosomal protein (RILP) (Cantalupo, Alifano, Roberti, Bruni, & Bucci, 2001;Harrison, Bucci, Vieira, Schroer, & Grinstein, 2003;Jordens et al, 2001), which serves as a bridge between microtubule Arp2/3 complex (Pollitt & Insall, 2009;Rougerie, Miskolci, & Cox, 2013).…”
Section: Effectors Of Rab7 Isotypesmentioning
confidence: 99%
“…The EhAGCK1 knockdown mutants used in the study were generated using an approach that affects the expression of off-target genes (77). It has been suggested that E. histolytica phosphatidylinositol 3-phosphate (PI3P) membrane glycerophospholipid-binding proteins such as Vsps and SNXs might be involved in trogocytosis and phagocytosis (78). Further work is still needed to determine which mechanisms are specific to E. histolytica trogocytosis.…”
Section: The Molecular Mechanism Underlying Trogocytosismentioning
confidence: 99%